##### Simplifying an exponential equation

 Mathematics Tutor: None Selected Time limit: 1 Day

42x^-7 y^6 / 15x^3 y^-4

Aug 10th, 2015

[(42/15)x^(7-3)] *[y^(6- -4) ] =[(42/15)x^(7-3)] *[y^(6+4) ]

=(42/15)X^4 * y^10

Aug 10th, 2015

[(42/15)x^(7-3)] *[y^(6- -4) ] =[(42/15)x^(7-3)] *[y^(6+4) ]

=(42/15)X^4 * y^10;

42 /15=14/5=2.8

therefore (42/15)X^4 * y^10

=(2.8)X^4 * y^10

=2.8X^4 * y^10

Aug 10th, 2015

Thank you! I only have one left, where would I go to get help with that?

Aug 10th, 2015

Post it again as a paid a question , I will place a cheaper price and you select me to answer........or post it as a prepaid question . You can also post it here so that I answer it for you.

Aug 10th, 2015

is easier as a prepaid question.

Aug 10th, 2015

Do you have more questions apart from the remaining one?

Aug 10th, 2015

Hello ,can you post it so that I help before I go offline..........I am alsost signing off ,hurry please.

Aug 10th, 2015

Just post it here . Is it okay with you?

Aug 10th, 2015

...
Aug 10th, 2015
...
Aug 10th, 2015
Dec 4th, 2016
check_circle